Efforts to Implement the Project to Strengthen the Profile of Pancasila Students as Student’s Character - Firdiansyah, Firdiansyah; Apriana, Leni; Emilia, Emilia (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to analyse the implementation of the Profile Strengthening Project Pancasila Students (P5) as an effort to strengthen the character of students includes design; management; processing assessments and reporting results; evaluate and act carry on. Study This use method qualitative descriptive in School State Policy 241 City of Palembang year 2023. Technique data collection in the form of interviews, observation and documentation. Data analysed with interactive techniques including data collection, data condensation, presentation data, and conclusions/verification. The research results show that 1) design P5 consists from form team, identify readiness school, determine dimensions character Profile Student Pancasila Which want to strengthened, determine theme, plan time, channel, assessment, And make module; 2) management P5 includes provocation and contextualization, P5 action, and celebration of learning outcomes; 3) Processing assessment and reporting P5 results includes collecting and processing results assessment and preparation of project reports; 4) evaluation and follow-up P5 in the form of strengthening character and continuing good habits with the Mari program In action. Through P5 actions, we can strengthen the character dimensions of the Pancasila Student Profile to students, especially those who are faithful, devoted to God Almighty and have noble character, work together, be independent, have global diversity, think critically and creative.